Whole mtGenome analysis in United Arab Emirates populations. Issue 1 (December 2019) - Almheiri, R.; Bakri, M.; Alghafri, R.; Goodwin, W.
Abstract: Mitochondrial DNA analysis has earned its place in the field of genetics for providing a new window into understanding population ancestry. Its ability to produce results from minimal or decayed samples where nucleus DNA profiling proves are difficult is an additional benefit to forensic genetics. A total of 150 whole blood samples were collected on FTA paper, from Arabs population in United Arab Emirates, including inhabitants from rural regions. Both extraction of whole blood samples using PrepFiler® as well as direct amplification of mtDNA control region from purified 1.2 mm disc of FTA card stained with blood were attempted in this study. Quantity of the amplified control region was estimated using gel electrophoresis. Three sets of primers were used afterward to sequence purified products of amplified control region of mtDNA using Sanger sequencing method. 150 mtGenome sequences were obtained for UAE Arabs population, generated using MPS technology – Ion™ 5S. Concordance with control region sequences obtained using Sanger Sequencing approach was investigated. Resulted haplotypes were compared against worldwide mtDNA database (EMPOP) and estimated haplotypes frequency is shown in this study. As a forensic lab, non-probative challenging bone samples were tested to highlight the potentials value of using MPS technology – Ion™ 5S. This study shows the first mtGenome data generated for UAE Arabs population which helps extending the current available mtDNA control region database. As a result, this study shows great value of implementing MPS in the routine work in forensic genetics at Dubai Police.